Numerical investigation on radiative and evaporative characteristics of a liquid droplet radiator through Monte-Carlo method. (5th November 2022) - Yang, Linyi; Wang, Chenglong; Qin, Hao; Zhang, Dalin; Tian, Wenxi; Su, G.H.; Qiu, Suizheng
Highlights: Novel method was performed to obtain the evaporative loss of droplet layers. Evaporation loss rate in the edge region of the droplet layer can be negative. Working performance of droplet layers for space applications was studied. Abstract: The liquid droplet radiator (LDR), a frameless heat dissipation device, is regarded as a preferred heat control solution for megawatt-scale space power systems. Accurate calculation of evaporation loss in the droplet layer is important for LDR systems since it determines the operating life of the LDR. In the present work, a novel model based on the Monte-Carlo Method (MCM) was developed to calculate the evaporation loss of the droplet layer. Compared to previous work in the literature, this model considers the evaporation loss of the droplet layer in the thickness and length directions. The radiative heat transfer characteristics of the droplet layer are also studied. The effects of optical thickness, operation temperature, and flight time on the droplet layer's heat transfer and evaporation processes were obtained and analyzed. The calculation results show that the temperature difference between the center and the edge of the droplet layer is larger than 65 K when the optical thickness is greater than 5. The heat dissipation power no longer varies significantly when the optical thickness of the droplet layer is greater than 6. The region with a negative specific evaporation loss rate accounts for 55.2 %, 58.2 %, and 0 for the whole droplet layer with optical thicknesses of 10, 5, and 0.2, respectively. The main evaporative loss comes from the beginning 5 m of the droplet layer. This paper may provide favorable reference to the design and optimization of the LDR systems.